How Revealing Rankings Affects Student Attitude and Performance in a Peer Review Learning Environment - Papadopoulos, Pantelis M.; Lagkas, Thomas; Demetriadis, Stavros N. (Computer Supported Education, 2016)
This paper investigates the possible benefits as well as the overall impact on the behaviour of students within a learning environment, which is based on double-blinding reviewing of freely selected peer works. Fifty-six sophomore students majoring in Informatics and Telecommunications Engineering volunteered to participate in the study. The experiment was conducted in a controlled environment, according to which students were divided into three groups of different conditions: control, usage data, usage and ranking data. No additional information was made available to students in the control condition. The students that participated in the other two conditions were provided with their usage information (logins, peer work viewed/reviewed, etc.), while members of the last group could also have access to ranking information about their positioning in their group, based on their usage data. According to our findings, students’ performance between the groups were comparable, however, the Ranking group revealed differences in the resulted behavior among its members. Specifically, awareness of ranking information mostly benefited students which were relatively in favor of ranking, motivating them to further engage and perform better than the rest of the group members.